Effect of changes of work stress electric drive crusher - Kutsenko, Y. (Енергетика і автоматика, 2015)
The influence of voltage fluctuation on the angular velocity of crushers. The possibility of direct start electric motor crushers and stability conditions of electric motors working in a production environment.